2012
DOI: 10.2337/diaspect.25.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Culturally and Linguistically Competent Health Coach Intervention for Chinese-American Patients With Diabetes

Abstract: Background. Type 2 diabetes is a growing concern among medically underserved Chinese Americans. However, very few interventions have been developed or adapted for Chinese Americans with diabetes. Objective. To use a participatory research approach to evaluate the effectiveness of a culturally tailored, linguistically appropriate model for diabetes care employing health coaches to improve A1C levels among Chinese-American patients in a federally qualified health center setting. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…31 In addition, providing financial incentives or paths to career advancement for MAs can help to overcome reluctance on their part and increase MA retention. 13 Finally, dissemination of lessons learned and strategies used are needed to enable other primary care practices to expand MA roles more smoothly and efficiently.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…31 In addition, providing financial incentives or paths to career advancement for MAs can help to overcome reluctance on their part and increase MA retention. 13 Finally, dissemination of lessons learned and strategies used are needed to enable other primary care practices to expand MA roles more smoothly and efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, Ferrer and colleagues 2 found that there was poor adoption of MA health coaching, and several randomized trials testing the effects of MA diabetes health coaches found no significant differences in hemoglobin A1C levels or hospitalizations between control and intervention group patients. 10,13,15,18 There is currently a limited understanding as to why there was success in some studies and not others.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18][19] Medical assistant health coaching could be a viable model for providing self-management support in primary care if its effectiveness were demonstrated across the most prevalent cardiovascular conditions. We conducted a randomized controlled trial to test the effectiveness of clinic-based medical assistant health coaching vs usual care to improve clinical indicators among low-income patients with uncontrolled type 2 diabetes, hypertension, and hyperlipidemia.…”
Section: Introductionmentioning
confidence: 99%